Innovation-based competitive differentiation amongst South African fibre to the home (FTTH) operators - Ntsandeni, Andiswa (My University, 2018)
Fibre-to-the-home (FTTH) as an access technology is viewed as vital for economic growth and competitiveness. The deployment of high speed networks and advanced access technologies is essential for continuous development of broadband in South Africa. FTTH is an access technology that has recently been deployed and adopted by different network providers in South Africa. South Africa is one of the developing countries attracting investments in the deployment of infrastructure where industry players are deploying fibre at a high rate with acquisition of smaller players. FTTH operators and service providers are challenged with competitive pressures within the market where competitiveness relies on the capacity to continually develop and implement unique innovative initiatives that will drive competitive advantage over its competitors. Competitive advantage is needed to achieve the organisation’s objectives. These innovative initiatives are required due to intense competition within the market which results in reduction of prices and margins. The purpose of this study is the exploration of innovation-based competitive differentiation from a South African FTTH provider perspective. The study aims to look at potential innovation differentiation amongst South African FTTH providers and how it can be applied in order to obtain a competitive advantage by looking at the factors that influence competitive advantage and barriers for innovation within the market. The study will provide knowledge and insights to develop an understanding of innovation for FTTH providers in a developing country such as South Africa. In this study, realistic data from the different network providers and service providers has been collected utilising a qualitative research method to investigate and conduct an in-depth analysis based on interviews with subject matter experts and managers from FTTH operators and service providers. Some propositions have been suggested as a validation for the proposed framework. The sample for the study has been drawn from the active FTTH network infrastructure operators and service providers based in Gauteng. The research findings indicate that the fibre-to-the-home market is a highly competitive environment with network providers and service providers offering various products and services to customers in order to meet customer needs. However, there are challenges with innovation based competitive differentiation since, currently, 3 competition is primarily based on the price of the broadband product. As a result, prices have been plummeting, leading to some service providers operating and selling their FTTH products with no margins or negative margins. KEYWORDS: Fibre-to-the-Home, FTTH, Innovation, Differentiation, Competition, Network Operators, Competitive Advantage.
A research report submitted to the Wits Business School in the University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in the field of Innovation Studies
Keywords: Fiber optics; Optical communications; Computer network